2015
DOI: 10.7494/geol.2015.41.3.285
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bottom sediment supplement on changes of soil properties and on the chemical composition of plants

Abstract: Abstract:The aim of the study was to assess the effect of bottom sediments on the selected properties of light soil as well as the content of trace elements in tested plants. The bottom sediments collected from the Besko reservoir were added to the soil in an amount of 5%, 10%, 30% and 50% of air-dried sediment, in relation to dry soil mass. The pot experiment was conducted on a light soil, with weak loamy sand grain size composition and slightly acid reaction, which was enriched with a supplement of bottom se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…As shown in multiple studies, if the material extracted from the bottom of the silted reservoir does not pose a threat to the environment, an environmentally justified reason for using such sediment is to use it as a structure-and soil-forming material for soilless grounds and wastelands (Tarnawski et al 2015, Baran et al 2016. Bottom sediments, in particular those that are neutral or alkaline and contain a high content of dust and clay fractions, can be used to increase the productivity of light and acid soils (Baran et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in multiple studies, if the material extracted from the bottom of the silted reservoir does not pose a threat to the environment, an environmentally justified reason for using such sediment is to use it as a structure-and soil-forming material for soilless grounds and wastelands (Tarnawski et al 2015, Baran et al 2016. Bottom sediments, in particular those that are neutral or alkaline and contain a high content of dust and clay fractions, can be used to increase the productivity of light and acid soils (Baran et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…And so, the mean concentrations of lead are from 20% to five times higher, mean concentrations of cadmiumfrom 33 to 55 times higher, while mean concentrations of nickel are from 1.4 to 3 times higher than the previously mentioned concentrations. The impact of the catchment use on the content of heavy metals in sediments of reservoirs is confirmed by the results of research by many authors [24,54,55]. Sojka et al [24] found, based on research on heavy metals in reservoirs located in the lowland area of western Poland, that heavy metal concentrations in bottom sediments are lower in the analyzed reservoirs located in agricultural catchment.…”
Section: Discussionmentioning
confidence: 56%
“…The Besko reservoir is trough-like, and it was formed as a result of backing up the waters of the Wisłok river by a concrete dam in a narrow valley. The purpose of the reservoir is to enable water intake for public purposes (neighboring cities and villages), for energy purposes, and also to run fish farms (Baran et al 2011 ; Tarnawski et al 2015 ). An important purpose of this facility is to equalize the base flows and particularly the instream (biological) flow.…”
Section: Methodsmentioning
confidence: 99%